DEAD WORDS OF MINANGKABAUNESE USED IN BASA AMPEK BALAI TAPAN - Oca wulandari; Jufrizal Jufrizal (Universitas Negeri Padang, 2019)
Tapan dialect is one of dialect of Minangkabaunese in Tapan. There are so many dead words or words that been forgotten by Tapan society nowaday. Words that are no longer used or dead words that happen day by day can make language death happen. This paper explains the causes of dead words in Basa Ampek Balai Tapan subdistrict and explain the word class of those dead words. According to the result of analysis it can be concluded that there are many factors that causes dead words occur in Basa Ampek Balai Tapan dialect, Pesisir Selatan regency such as language contact, the influence of globalization, feel proud of using lingua franca, the objects do not exist anyomore, less care on their own dialect and the words sound impolite to hear.This paper agrees that endangered languages are worth saving so we need to be aware about many factors contribute to language death.Keywords : dead words, dead language, dialect, Minangkabaunese